Design and evaluation of low-power switching power supplies using a zero-voltage boost converter with a snubber circuit - Savangboon, Teerawut; Chaithanakulwat, Arckarakit; Thungsuk, Nuttee; Tanaram, Thaweesak; Sardyoung, Papol (Edelweiss Applied Science and Technology, 2024)
Switching power supplies are widely popular because they are sufficiently small to fit all types of electrical appliances. Adjusting the pulse width modulation (PWM) of the switching power supply under high-frequency conditions often causes switching losses. PWM also causes electromagnetic interference (EMI) under high-frequency switching conditions. These problems can be solved using soft switching, which can adequately reduce the losses under switching conditions and EMI-induced noise. Therefore, this study describes the design and evaluation of a zero-voltage boost converter with a snubber circuit for a low-power switching power supply, which reduces the performance loss of the switching power supply under high-frequency conditions. This study was divided into two main parts. The first part focuses on the use of TMS320F28377S microcontrollers, which are outstanding in their precise control and can simulate switching within the MATLAB/Simulink program environment, and studies the switching behavior of boost converters in detail, making the switching power supply high performance and reliable. The second part focuses on evaluating the performance of the boost converter under different conditions, consisting of a state stimulated by the snubber circuit and a non-stimulated state by the snubber circuit. However, the evaluation showed that the boost converter in the space activated by the snubber circuit had an 85.16% increase in performance, which was 6.75% higher than that in the no-stimulation state with the snubber circuit. Similarly, the switching power supply can control and maintain a constant voltage, and this effect is satisfactory and reliable.